The Social Organization and Interpersonal Dynamics of Crack-for-Cars Transactions in Louisianna, USA - Copes, Heith (The British journal of criminology, 2007)
Participation in street-life structures and creates opportunities for acquiring a cache of illicit goods. While cash is the primary means of obtaining illegal drugs, more innovative hustles' have recently emerged. Specifically, one strategy involves individuals exchanging the temporary use of their vehicles for crack cocaine. We use in-depth interviews with 19 inmates and 27 active crack cocaine users to describe the social organization and interpersonal dynamics of this phenomenon, herein referred to as rock rentals. In addition, we examine how the rental contract is structured, vehicle owners' and borrowers' motivations for engaging in the trade and how violations are remedied